The Urgenda Case in the Netherlands on Climate Change and the Problems of Multilevel Constitutionalism - Gerhard van der Schyff (Constitutional Review, 2020)
This contribution analyses the Urgenda judgments in the Netherlands which ordered the state to reduce the national emissions of greenhouse gasses by 25% by the end of 2020. In arriving at this conclusion, the courts relied heavily on international law, which was applied indirectly and directly to the case. The analysis shows various incongruencies and gaps in the judgments’ legal grounds and reasoning, and suggests that a focus on the Constitution is needed as well in addressing such important issues. This will require long overdue reform of the bar on constitutional review in order to stimulate a strong national legal culture based on the Constitution.